2013
DOI: 10.1177/1535370213489446
|View full text |Cite
|
Sign up to set email alerts
|

Role of p62/SQSTM1 in liver physiology and pathogenesis

Abstract: p62/sequestosome-1/A170/ZIP (hereafter referred to as p62) is a scaffold protein that has multiple functions, such as signal transduction, cell proliferation, cell survival, cell death, inflammation, tumorigenesis, and oxidative stress response. While p62 is an autophagy substrate and is degraded by autophagy, p62 serves as an autophagy receptor for selective autophagic clearance of protein aggregates and organelles. Moreover, p62 functions as a signaling hub for various signaling pathways, including NF-κB, Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 152 publications
(469 reference statements)
4
98
1
1
Order By: Relevance
“…These altered forms of the protein were found to localize to non-SG structures, characterized by the presence of ubiquitin and the p62/sequestosome-1 protein (SQSTM1), and the absence of a vimentin cage. SQSTM1 is a scaffold protein containing several protein interaction domains and with multiple functions in signal transduction, cell death and inflammation (54,55). A growing body of evidence suggests in particular a role for p62 in directing ubiquitinated proteins for autophagic destruction, and as a platform for NF-B signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These altered forms of the protein were found to localize to non-SG structures, characterized by the presence of ubiquitin and the p62/sequestosome-1 protein (SQSTM1), and the absence of a vimentin cage. SQSTM1 is a scaffold protein containing several protein interaction domains and with multiple functions in signal transduction, cell death and inflammation (54,55). A growing body of evidence suggests in particular a role for p62 in directing ubiquitinated proteins for autophagic destruction, and as a platform for NF-B signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Those domains enable p62 to regulate kinase-activated and ubiquitin-mediated signaling pathways [46] . The PB1 domain of p62 interacts with some protein kinases, including ERK1/2, MEKK3 and MEK5 [11] . It has been reported that p62 is involved in regulating ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the PB1 domain of p62 interacts with extracellular signal-regulated kinase (ERK) and maintains low ERK activity under normal conditions [11,14,15] . Consistent with these findings, ERK1/2 activity is enhanced in p62-deficient mice [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequestosome 1 (SQSTM1 or p62) is a multifunctional adapter protein. Although the full spectrum of its functions is not known, there is growing evidence that p62 regulates apoptosis and cell survival through the catabolic metabolism of molecules involved in NF-kB, mTOR, MAPK, and possibly also other signaling pathways (4)(5)(6)(7). p62 localizes to the membranes of autophagosomes and is itself cleared by autophagy (6,7).…”
Section: Introductionmentioning
confidence: 99%